Perkembangan Sektor Keuangan Islam dan Pertumbuhan Ekonomi: Studi Empiris Negara OKI - Cupian Cupian; Arie Febriansyah; Alfiah Hasanah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study explores the effect of the development of Islamic Financial sectors toward the economic growth of ten Islamic countries based on the Global Islamic Economy Indicator (GIEI) from 2014 to 2018. The Islamic financial sectors consist of issuing covering finance represented by the value of Islamic funds and the value of outstanding Sukuk. The governance factor is represented by the number of Islamic finance regulations and the number of Islamic finance scholars. The awareness is represented by some institution education about Islamic Finance and several news/articles about Islamic finance. The Islamic social fund is represented by the fund of Zakat and Charities, and the fund of Corporate Social Responsibility (CSR). This research use panel data and a random effect for analyses. The result shows that three variables positively contribute to economic growth; the value of outstanding Sukuks, the number of Islamic finance regulations, and the number of Islamic educations about Islamic finance. Meanwhile, the number of Islamic finance regulations, the number of Islamic finance scholars, the number of news/articles, the value of zakat and charity, and the CSR scores index do not significantly contribute to the economic growth of ten Islamic countries.